Designing POCAB Using Powerpoint as a Medium for Teaching Adjectives to the 7th Grade Students - Calvin Lim; Dwi Riyanti; Wardah Wardah (TLEMC (Teaching and Learning English in Multicultural Contexts), 2022)
This paper aims to describe the result of the project of creating the POCAB (PowerPoint Vocabulary) game as a medium for teaching English adjective vocabulary. The main objective of the research was to create vocabulary exercises to assist the students in learning descriptive adjective vocabulary. The research method was development research involving four phases of the ADDIE (Analyze, Design, Develop, Implement, and Evaluation). The hyperlink features and slide animation from the Microsoft PowerPoint application were combined to create an attractive game in this research. This product was implemented for eleven students of 7th-grade students at SMP Sentosa Pemangkat, West Kalimantan. The research findings show that the POCAB game is applicable as a medium to teach vocabulary materials related to descriptive adjective vocabulary. It is proven by the high percentage of recommendations from both the teacher and students. This means the product is categorized as "very good." From the research result, it can be concluded that the POCAB game is applicable as a medium to teach descriptive adjective vocabulary and is categorized as an excellent product.Keywords: development research, POCAB game, media, descriptive adjective vocabularyÂ